An Analysis of Address Terms Received by Queen Elizabeth in The Prince Animated Series - Kasmaini, Kasmaini; Priambudi, Arif; Kurniawan, Ildi (Journal of Social Work and Science Education, 2023)
This study investigates address terms received by Queen Elizabeth in animated series entitled The Prince. It classifies address terms into seven types, namely first name, title plus last name, title only, last name, special nickname, pet name, and kinship term. It also identifies the social factors behind the use of certain address terms. Those factors are particular occasion, social status, gender, age, family relationship, occupational hierarchy, race, and degree of intimacy. The data were taken from the subtitles of this animated series. The results show that the most frequently used address terms were kinship terms with 37 (49%) occurrences. However, Queen Elizabeth in this animated series never received a first name, title plus last name, and last name as address terms. Addressing the queen in the series was mainly influenced by the gender of the addressee, familial ties, and the degree of intimacy between the addressers and the addressee. On the other hand, the address terms were never influenced by factors such as race, transactional status, occupational hierarchy, and age. The findings suggest that Queen Elizabeth received address terms that were mostly gender-specific and intimate. The majority of address terms that Queen Elizabeth received in this series came from her family members, while small minority of them were uttered by the servants and other characters who were not her family members.